Treatment Strategies in Childhood Craniopharyngioma - Puget, Stephanie (Frontiers in Endocrinology, 2012)
The surgical management of craniopharyngioma in children has been one of the most controversial topics in pediatric neurosurgery. In theory, based on its benign histology total surgical excision could provide a cure. However, the therapeutic goals for pediatric craniopharyngioma are not only the cure of the disease but also the preservation of function. It has been widely established that in some particular cases total excision could leads to inacceptable damages, especially those linked to hypothalamic functions. During the last 15 years, we observed worldwide a growing advocacy for less-invasive pediatric craniopharyngioma resection supported by international consensus conferences. The state-of-the-art in the surgical management of some craniopharyngioma is now turning to multi-modality treatment strategies (combination surgery and radiotherapy) aiming to limit morbidiy. Recent literature and our own experience helped to develop risk-adapted treatment strategies at initial diagnosis, respecting hypothalamic structures to provide optimal quality of life for these children. Following new algorithms of treatment, preliminary results with intention to spare the hypothalamus seem to be encouraging but the long-term clinical outcome in terms of post irradiation complications and relapse management is currently unknown.